Wat Buschmen trachten te behouden ... - Verpoorte, Alexander (Afrika Focus, 1996)
This article has a double goal. First, it tries to enlighten keynotions in Weiners book: inalienable possessions, brother-sister-relations, hierarchy and equality, cosmological authentication. Second, it relates the paradox of keeping-while-giving to the concept of possession and exchange among Southern African groups of hunters and gatherers. The article aims at clarifying the strengths and weaknesses of this paradox and contributing tot the ethnography of the Bushmen. KEY WORDS: Bushmen, inalienable possessions, exchange, Southern Africa, hunter-gatherers.